MAKNA KATA FASIK DALAM QS. AL-HUJURAT [49]:6 (Analisis Semiotika Roland Barthes) - Unggul Prayoga; Munawir (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2023)
This article examines the meaning of the word fasiq in Surah al-Ḥujurāt: 6. In conducting the research, the author used Roland Barthes’s theory of semiotics which has two stages (linguistic stages and mythological stages). The result was that fasiq means someone who leaves the right path because he violates religious rules. Then the second stage of looking for the meaning of myths gives rise to the meaning of the fasiq as a liar or a person who spreads hoax news. Then the second stage of looking for the meaning of myths gives rise to the meaning of the fasiq as a liar or a person who spreads hoax news